2020
DOI: 10.1371/journal.pone.0227444
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation of the early human remains from Quintana Roo, Yucatán Peninsula, Mexico: Contributions to the discussions about the settlement of the Americas

Abstract: The human settlement of the Americas has been a topic of intense debate for centuries, and there is still no consensus on the tempo and mode of early human dispersion across the continent. When trying to explain the biological diversity of early groups across North, Central and South America, studies have defended a wide range of dispersion models that tend to oversimplify the diversity observed across the continent. In this study, we aim to contribute to this debate by exploring the cranial morphological affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
(135 reference statements)
3
4
1
1
Order By: Relevance
“…According to these authors, the Quintana Roo material demonstrates a very high degree of morphological and biological diversity among indigenous North Americans in the late Pleistocene and early Holocene, which far exceeds that typically observed among their counterparts in South America. The results of the current study—including the wide range of variation observed among North American samples, the clear separation of WL‐2 from at least some of her contemporaries in the US and Mexico, and the somewhat different associations she seems to exhibit depending on the analytical procedure and/or morphological aspects considered—align well with the general conclusions of Hubbe et al (2020). Moreover, even the seemingly contradictory finding that, unlike the Quintana Roo crania (and many other early North and South American specimens), WL‐2 appears quite similar to recent American Indians is potentially in line with the idea that early North American morphology varied widely, given that multiple different patterns of affinity might well be expected among the individuals in a highly diverse population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…According to these authors, the Quintana Roo material demonstrates a very high degree of morphological and biological diversity among indigenous North Americans in the late Pleistocene and early Holocene, which far exceeds that typically observed among their counterparts in South America. The results of the current study—including the wide range of variation observed among North American samples, the clear separation of WL‐2 from at least some of her contemporaries in the US and Mexico, and the somewhat different associations she seems to exhibit depending on the analytical procedure and/or morphological aspects considered—align well with the general conclusions of Hubbe et al (2020). Moreover, even the seemingly contradictory finding that, unlike the Quintana Roo crania (and many other early North and South American specimens), WL‐2 appears quite similar to recent American Indians is potentially in line with the idea that early North American morphology varied widely, given that multiple different patterns of affinity might well be expected among the individuals in a highly diverse population.…”
Section: Discussionsupporting
confidence: 89%
“…That several aspects of cranial size and shape in WL‐2 are quite distinct from many of her North and South American contemporaries further supports the idea of significant morphological variation among Paleoindians as a whole, which has been noted by previous authors (e.g., Hubbe et al, 2020; Jantz & Owsley, 2001). Recent work by Hubbe et al (2020) documents extensive morphological variation among a series of Paleoindian crania from Quintana Roo, Mexico, particularly when compared with South American Paleoindians, and found that these individuals exhibited surprisingly different patterns of affinity to early American and modern reference samples. According to these authors, the Quintana Roo material demonstrates a very high degree of morphological and biological diversity among indigenous North Americans in the late Pleistocene and early Holocene, which far exceeds that typically observed among their counterparts in South America.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Because distances invariably take the information of all the variables and, in the case of MMD and Euclidean distance, variables are all equally weighted, they are prone to be more affected by outlier values in one or few variables. PCA analyses, on the other hand, explores the most relevant axes of covariance among all variables, which results in the noise caused by outliers in one or few variables to not be present in the most important PCs (see a similar discussion in Hubbe et al, 2020). Therefore, the PCA offers a check for the reliability of distance analyses and complement well the analyses based on pairwise distances.…”
Section: Methodsmentioning
confidence: 99%
“…One of the main challenges that arose from our interdisciplinary debate is the lack of hypotheses and models that can be tested from multiple disciplinary perspectives. On one hand, many studies about the origin of Native American biological diversity are overly focused on describing patterns of variation, 52 rather than testing specific hypotheses 53 . On the other hand, as pointed out by Dillehay, 54 most recent studies are not discussing new evidence in relation to previous models but rather dismissing them and proposing new ones (e.g., References 19,55 in Reference 54).…”
Section: The Interdisciplinary Debatementioning
confidence: 99%